Design and Validation of an Integrated Resilience and Play Therapy Training Model and Its Effect on Problem-Solving Skills and Mathematical Performance of Students - Mohebbi , Azam; Manavipor, Davod; Mohammadi, Akbar (Assessment and Practice in Educational Sciences, 2026)
The present study was conducted with the aim of designing and validating an integrated resilience and play therapy training model and examining its effect on problem-solving skills and mathematical performance among elementary school students. This research employed an exploratory mixed-methods design. In the qualitative phase, through thematic analysis and a review of theoretical foundations and prior studies, the components and content of the integrated training package were extracted. In the quantitative phase, a quasi-experimental design with pretest–posttest–follow-up and a control group was applied. The statistical population consisted of all fourth-grade female elementary students in Tehran during the 2024–2025 academic year. A total of 30 students from two schools were selected and randomly assigned to the groups. The experimental group received 10 sessions of integrated training, while the control group remained on the waiting list. The data collection instruments included the Problem-Solving Inventory by Heppner and Petersen (1982) and the TIMSS Mathematics Performance Test. Findings from the qualitative phase indicated that the extracted themes comprised personal resilience resources, emotional resilience skills, cognitive resilience skills, social resilience skills, environmental factors of resilience, principles of play therapy, emotional functions of play therapy, cognitive functions of play therapy, social functions of play therapy, humanistic principles of play therapy, cognitive-developmental principles of play therapy, and cognitive-emotional functions of play therapy. Findings from the quantitative phase revealed that the integrated resilience and play therapy training significantly and positively affected students’ problem-solving skills and mathematical performance. Moreover, these effects persisted not only in the posttest but also at the follow-up stage. Based on the results, it can be concluded that the integrated resilience and play therapy training package serves as an effective model for enhancing students’ cognitive and academic competencies.